Association Between BoLA-DRB3.2 Polymorphism and Bovine Papillomavirus Infection for Bladder Tumor Risk in Podolica Cattle - Longeri, Maria; Russo, Valeria; Strillacci, Maria Giuseppina; Perillo, Antonella; Carisetti, Michela; Cozzi, Maria Cristina; Neola, Benedetto; Roperto, Sante (Frontiers in Veterinary Science, 2021)
Abstract: Blood samples from 260 unrelated cattle (132 animals affected by papillomavirus-associated bladder tumors and 128 healthy) were genotyped using the classic PCR/RFLP method to screen MHC class II BoLA-DRB3.2 polymorphism. The DRB3*22 allele was significantly (p  0.01) detected in healthy cattle, thus appearing to have a negative association (protective effect) with virus infection of the urinary bladder known to represent a bladder tumor risk for cattle living free at pasture. Considering the two sequence alleles identified in animals carrying DRB3*22, DRB3*011:01 allele from samples of animals harboring the unexpressed BPV-2 E5 gene was characterized by amino acid residues believed to have a protective effect against BPV infection such as Arginine at position 71 (R71) in pocket 4, Histidine at position 11 (H11) in pocket 6, both Glutamine at position 9 (Q9) and Serine at position 57 (S57) in pocket 9 of the antigen binding groove. The DRB3*011:02v allele from affected animals was characterized by amino acids believed to be susceptibility residues such as Lysine (K71), Tyrosine (Y11), Glutamic acid (E9), and Aspartic acid (D57) in these pockets. These results suggest that animals harboring the DRB3*011:01 allele may have a lower risk of BPV infection and, consequently, a reduced risk of bladder tumors.